The rural entrepreneurial venture - Van Horn, Richard L.; Harvey, Michael G. (Journal of Business Venturing, 1998)
Non-metropolitan areas have been attracting the attention of entrepreneurs due to the low cost of doing business and advances in telecommunications. In metropolitan settings, the entrepreneur typically employs a network of professionals and has access to expertise that can easily be consulted to help remedy problems facing the organization. In a rural location, entrepreneurs must develop a means to augment the expertise assembled in the firm and in the local area. Information becomes the critical variable in strengthening the competitiveness of rural entrepreneurs. The evidence strongly supports the view that critical success factors exist for entrepreneurial ventures, that information systems impact many of these critical success factors, and that rural ventures can benefit greatly from an effective expert information system. This paper examines the issues associated with improving the gathering and processing of information to enhance the structure, resources, and decision-making capabilities of rural entrepreneurs. Several concepts are presented that should provide assistance for examining the issues. These concepts are then integrated into the model, the entrepreneurial virtual megafirm (EVM), designed to provide infrastructure to enhance the effectiveness of rural entrepreneurs.